2015
DOI: 10.4103/0366-6999.162510
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of the SYNergy Between Percutaneous Coronary Intervention with TAXus and Cardiac Surgery Score II for Long-term Mortality in Patients with Three-vessel Coronary Artery Disease Undergoing Percutaneous Coronary Intervention Treated with Second-generation Drug-eluting Stents

Abstract: Background:The SYNergy between percutaneous coronary intervention with TAXus and cardiac surgery Score II (SS-II) can well predict 4-year mortality in patients with complex coronary artery disease (CAD), and guide decision-making between coronary artery bypass graft surgery and percutaneous coronary intervention (PCI). However, there is lack of data regarding the utility of the SS-II in patients with three-vessel CAD undergoing PCI treated with second-generation drug-eluting stents (DES). The purpose of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Recent studies have shown that PCI is associated with a similar risk of death compared with CABG in patients with multivessel disease,[ 19 20 ] especially in patients with lower SYNTAX score. [ 21 22 ] However, these studies focused only on TVD patients, not PTVD patients. Our results showed that PCI was associated with equal long-term benefit compared with CABG for all-cause death and cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that PCI is associated with a similar risk of death compared with CABG in patients with multivessel disease,[ 19 20 ] especially in patients with lower SYNTAX score. [ 21 22 ] However, these studies focused only on TVD patients, not PTVD patients. Our results showed that PCI was associated with equal long-term benefit compared with CABG for all-cause death and cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with multivessel coronary disease, percutaneous coronary intervention (PCI) frequently involves incomplete revascularization (IR) because of coronary anatomy complexity or coexisting serious clinical conditions. [ 1 2 3 ] The prognostic impact of IR after PCI had been inconsistent among studies,[ 4 5 6 7 ] and one potential explanation was due to the lack of consent definition of IR. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…He и соавт. [32], у пациентов, чьи показатели соответствуют низкому, среднему и высокому терцилям SYNTAX score II, 5-летняя смертность составляла 1,6; 3,2 и 8,6 % соответственно, сердечнососудистая смертность -0,5; 1,9 и 5,2 % соответственно. При многофакторном анализе SYNTAX score II был независимым предиктором 5-летней смертности (относительный риск 2,45 при 95 % ДИ от 1,38 до 4,36;…”
Section: Discussionunclassified